Isolation and identification of microbial contaminations along the dairy value chain in gwaliorregion of Madhya Pradesh - RAJESH SINGH TOMAR; MONIKA GUPTA; RAGHVENDRA KUMAR MISHRA (International Journal of Pharma and Bio Sciences, 2017)
Milk is a natural and rich resource of minerals, vitamins, protein etc. Milk contamination is a very serious public issue, because millions of people especially children all over the world consume dairy products daily. An extensive study was carried out in Gwalior region of Madhya Pradesh, India. The study was to determine the various Milk handling practices and microbial contamination in various milk samples collected from dairy, milk parlor, and small shops. A total of 90 milk samples were collected from four different areas in Gwalior for the isolation and identification of microbes, from February 2016 to April 2016. Previously described standard protocols were adapted for the isolation and cultivation of microbes. Different biochemical assays like IMViC test, Catalase test, Oxidaxe test, and selective media were used to identify microbes in the milk samples. The results of the study showed that the presence of bacterial contamination (gram positive and negative types of microbes) in raw milk and pasteurized milk result from unhygienic practices during the pre-milking and storage stage. 72 samples were contaminated with Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa However, some more bacterial colonies were also observed, but the results are not stable. Also, drug resistant bacteria against Ampicillin and Tetracyclin were reported. On the basis of the present study, it is suggested that dairy farm, dairy shops, and milk parlors must improve the hygienic and storage condition of milk. In addition, public education must be given to all stakeholders in dairy industry on milking and post harvest handling of milk, to curtail the likely losses due to refusal of spoiled milk and milk-borne pathogens resulting from contamination of milk.